Pendampingan Literasi Sadar Hukum bagi Santri Asrama Sunan Muria Pondok Pesantren Sunan Drajat - Karmuji Karmuji; Gangga Listiawan; Ahmad Fahmi Khusaini; Muhammad Alwi Sihab (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2022)
Literacy is a necessity for all Indonesian people, because this is a basic need in honing skills in critical thinking, especially literacy in the field of law. We need to know that the Indonesian state is a legal state where all aspects of life are regulated by law, this makes it a separate obligation for all citizens to be aware of the law. our actions or behavior in this state must be in accordance with the corridors set by the law itself, and we all know that many of our people are still blind to the law and how massively they use violence as a way out in solving problems. Legal awareness literacy assistance for students in the Sunan Muria dormitory at the Sunan Drajat Islamic Boarding School Lamongan is the best step in increasing human resources who have legal awareness themselves, how do we cadre young students who will later become influencers for the community who incidentally lack of awareness of the law. This legal literacy assistance is through the presentation of material with an interactive dialogue system so that students can be more optimal in capturing and understanding the material presented.